121k views
0 votes
What is the solution to the equation 3 sqrt (5x-4) = 3 sqrt (7x+8) ? x = –6 x = –1 x = 1 x = 2

2 Answers

3 votes

Answer:

A. x=-6

Explanation:

Hope this helps!! Have a great day!! ❤

User Hendryanw
by
5.8k points
7 votes

Answer:

-6 = x

Explanation:

3 sqrt (5x-4) = 3 sqrt (7x+8)

Divide each side by 3

3/3 sqrt (5x-4) = 3/3 sqrt (7x+8)

sqrt (5x-4) = sqrt (7x+8)

Square each side

(sqrt (5x-4))^2 = ( sqrt (7x+8) )^2

5x-4 = 7x+8

Subtract 5x from each side

5x-5x-4 = 7x-5x+8

-4 = 2x+8

Subtract 8 from each side

-4-8 = 2x+8-8

-12 = 2x

Divide by 2

-12/2 = 2x/2

-6 = x

User Sergiuz
by
5.0k points